2021
DOI: 10.4049/jimmunol.1900975
|View full text |Cite
|
Sign up to set email alerts
|

Pinaverium Bromide Attenuates Lipopolysaccharide-Induced Excessive Systemic Inflammation via Inhibiting Neutrophil Priming

Abstract: Dominant infiltration of neutrophils is a hallmark of many inflammatory diseases, especially in septic shock. IL-1β as one of the most early released proinflammatory cytokine in neutrophil, plays a pivotal role in the progress of sepsis. In this study, we built a high-throughput–compatible drug screen assay platform based on our newly constructed reporter C57BL/6 mice, pIL1-DsRed, expressing the DsRed gene under the control of the IL-1β promoter. After screening 1200 U.S. Food and Drug Administration–approved … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…Pinaverium bromide, a gastrointestinal (GI)-selective calcium channel antagonist, inhibits the influx of calcium into intestinal smooth muscle cells, thus relieving the contraction of intestinal smooth muscles, defecation-associated abdominal pain, and discomfort in patients with irritable bowel syndrome (IBS) . In recent years, pinaverium bromide was found to attenuate lipopolysaccharide (LPS)-induced excessive systemic inflammation via inhibiting neutrophil priming and protected the liver and lung from LPS-induced damage and reduced organ-specific inflammatory responses . However, there is no report on the antibacterial activity of pinaverium bromide, either for Gram-positive or Gram-negative bacteria.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pinaverium bromide, a gastrointestinal (GI)-selective calcium channel antagonist, inhibits the influx of calcium into intestinal smooth muscle cells, thus relieving the contraction of intestinal smooth muscles, defecation-associated abdominal pain, and discomfort in patients with irritable bowel syndrome (IBS) . In recent years, pinaverium bromide was found to attenuate lipopolysaccharide (LPS)-induced excessive systemic inflammation via inhibiting neutrophil priming and protected the liver and lung from LPS-induced damage and reduced organ-specific inflammatory responses . However, there is no report on the antibacterial activity of pinaverium bromide, either for Gram-positive or Gram-negative bacteria.…”
Section: Discussionmentioning
confidence: 99%
“…14 In recent years, pinaverium bromide was found to attenuate lipopolysaccharide (LPS)-induced excessive systemic inflammation via inhibiting neutrophil priming and protected the liver and lung from LPS-induced damage and reduced organ-specific inflammatory responses. 15 However, there is no report on the antibacterial activity of pinaverium bromide, either for Grampositive or Gram-negative bacteria. This study first found that pinaverium bromide had antibacterial activity against S. aureus and E. faecalis.…”
Section: ■ Discussionmentioning
confidence: 99%